2000
DOI: 10.1021/es001087r
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Changes in Model and Phytoplankton Membranes in the Presence of Aquatic Humic Substances

Abstract: Aquatic humic and fulvic acids can increase the permeability of biological membranes to lipophilic solutes. In in vivo experiments, passive diffusion of fluorescein diacetate (FDA) into the green alga Selenastrum capricornutum increased in the presence of Suwannee River humic and fulvic acids at pH 5 (humic > fulvic) but not at pH 7. The observation of enhanced diffusion at the lower pH is consistent with adsorption measurements, which showed that the association of humic and fulvic acids with the algal surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
172
1
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(185 citation statements)
references
References 21 publications
9
172
1
3
Order By: Relevance
“…Hence, the adsorbed humic substances might affect the properties of the algal surface by enhancing membrane permeability of both lipophilic metal complexes (24) and hydrophilic substances (25), by increasing the negative surface charge (6,11), and by adding the additional binding sites (10,11,26).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the adsorbed humic substances might affect the properties of the algal surface by enhancing membrane permeability of both lipophilic metal complexes (24) and hydrophilic substances (25), by increasing the negative surface charge (6,11), and by adding the additional binding sites (10,11,26).…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that, due to its surfactant-like properties, humic acid may intercalate among membrane phospholipids, resulting in a decrease in lipid-lipid interactions and an overall increase in membrane permeability (38). In such a case, an effect is likely to be observed for the SRHA, while no influence would be expected for the polysaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory-based experimental work, mainly with well-characterised pre-isolated fulvic and humic acids, demonstrated the key yet dual role of the DOM in metal uptake by algae. Humic substances decrease metal uptake by complexing metals in the medium, [7][8][9][10][11][12][13] but they can increase the adsorbed or internalised metal by adsorbing to the algal surfaces, [14][15][16] enhancing the negative charge [11,14,16] and adding additional binding sites on the algal cell surface that were proposed to contribute to increased Pb uptake. [11,12] A non-humic fraction, for example extracellular polymeric substances, representing up to 25% of DOM in natural waters [17] has received very little attention in metal uptake studies.…”
Section: Introductionmentioning
confidence: 99%